Drug Compliance and Psychosocial Wellbeing of Patients with Mental Illness in Ibadan (2022)
The study looked at medicine adherence and psychosocial well-being in patients with mental illnesses at Adeoyo State Hospital. Ring Road, Ibadan. A descriptive survey design was used in the investigation. One hundred and twenty (120) people with mental illnesses who visit Adeoyo State Hospital. Ring Road. Ibadan. Were purposefully chosen. For data gathering, a customised questionnaire was employed. Data for demographic parameters were analysed using percentage distribution and frequency counts, and Pearson Product Moment Correlational Analysis (PPMC) was used to test hypotheses at p = 0.05. The study found a strong link between medication compliance and psychological well-being in mentally ill individuals (r=,275. n=!20, p (.002).05). It was also shown that there was a substantial association between medication compliance and respondents' social well-being (r=.327, n=l20, p (.001).05). Il was recommended that patients with mental illnesses be monitored lo ensure drug compliance. Medical social workers are needed to educate the general population and society about the consequences of drug noncompliance.